2019
DOI: 10.18639/rabm.2019.959614
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Triad RANK/ RANKL/ OPG in Mandible and Femur of Wistar Rats (Rattus norvegicus) With Type 2 Diabetes Mellitus

Abstract: A successful treatment of dental implant needs a good jaw bone support, which depends on healthy bone metabolism. Bone metabolism can be affected by Diabetes Mellitus (DM). It may trigger various complications, including osteoporosis. Molecular triads consisting of Receptor Activator of NF-kappaB (RANK), Activator of nF-κB Ligand (RANKL), and osteoprotegerin (OPG), have an important role in the formation, function, and osteoclast survival. In this study, molecular triads were observed on mandible and femur bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Conversely, a decrease in OPG expression or an increase in RANKL expression can lead to pathological bone resorption characterized by an increase in the RANKL/OPG ratio. 16,18,32 This study found that the value of the RANKL/OPG ratio in the DM group was significantly lower than in the osteoporosis and control groups. This is probably caused by hyperglycemia which can cause a significant decrease in the RANKL/OPG ratio produced by osteoblasts.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Conversely, a decrease in OPG expression or an increase in RANKL expression can lead to pathological bone resorption characterized by an increase in the RANKL/OPG ratio. 16,18,32 This study found that the value of the RANKL/OPG ratio in the DM group was significantly lower than in the osteoporosis and control groups. This is probably caused by hyperglycemia which can cause a significant decrease in the RANKL/OPG ratio produced by osteoblasts.…”
Section: Discussionmentioning
confidence: 71%
“…Conversely, a decrease in OPG expression or an increase in RANKL expression can lead to pathological bone resorption characterized by an increase in the RANKL/OPG ratio. 16 18 32 …”
Section: Discussionmentioning
confidence: 99%